Perinatal outcomes and related factors: social class differences within and between geographical areas. Issue 4 (December 1986) - Elbourne, D; Pritchard, C; Dauncey, M
Abstract : This paper makes use of the opportunity provided by comparable obstetric data bases to examine area and social class variations in perinatal outcome and associated factors in areas smaller than those usually reported. Analyses are based on singleton births to primiparous residents in the catchment areas of the Aberdeen Maternity and Neonatal Database (n = 4948) and the Cardiff Births Survey (n = 11893) between 1976 and 1981. The factors considered relate to the obstetric population (height, age, and smoking), obstetric practice (induction and assisted delivery), and perinatal outcome (curtailed gestation, low birthweight, and perinatal death). Our analysis confirms the existence of both area and social class differences and suggests that, except in the case of teenage pregnancy and smoking, the association observed between those factors and area and social class are largely independent of each other.